Pengaruh Penerapan Pendidikan dan Pelatihan (Diklat) Online serta Motivasi Kerja terhadap Kinerja Pegawai Penunjang Medis - Agustina Ni Made Setiawati; Suandari P.V.L; Wardhana Z.F (Jurnal Manajemen Kesehatan Indonesia, 2021)
Hospital nowadays is demanded to be able to give a good, qualified, and as standard service to the society such as medical supporting service, training and education program application and working motivation which is one of the factors that can improve the performance of medical supporting employee in the hospital because the optimal performance of medical supporting employee is needed by the hospital a lot. This research aims to know about the effect of online training and education program application and also working motivation to performance of medical supporting employee in BaliMed hospital Denpasar. This research used quantitative approach. The sample taking technique in this research used proportional random sampling. The instrument of this research used questionnaire, the data analysis test that was used to solve the problem in this research was multiple line regression test. Based on the data analysis result, it is obtained that online training and education program application and working motivation have significant positive effect to the performance of medical supporting employee with the tcount of online training and education program application 4,568 and working motivation with the tcount 4,416 and also determination data 0,571 or 57,1% and the significance score 0,000 with α = 5 % (0,000 < 0,05), so the variable of training and education program and working motivation have significant and positive effect to the performance of medical supporting employees in BaliMed hospital Denpasar.